PENGERTIAN, DASAR-DASAR DAN CIRI-CIRI FILSAFAT - Samuji Samuji (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2022)
Understanding philosophy can be reviewed etymologically and terminology. The word philosophy comes from the Greek which is a compound word Philosophia or Philosophos. The word consists of two words namely philos (philein) and Sophia. The word Philos means love (love), while Sophia or sophos means knowledge, truth, wisdom or wisdom (wisdom). So etymologically philosophy means love of knowledge, truth or wisdom. There are 3 (three) foundations in philosophy, namely the ontology basis, the epistemological basis and the axiological basis. Meanwhile, according to Suprapto Wirodiningrat in Surajiyo (2012: 13), there are 3 (three) characteristics of philosophy, namely; Thorough, basic and speculative.